2019
DOI: 10.1002/advs.201901152
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP2 Plays an Essential Role in Cognitive Development during Early Life

Abstract: Identifying the mechanisms underlying cognitive development in early life is a critical objective. The expression of insulin‐like growth factor binding protein 2 (IGFBP2) in the hippocampus increases during neonatal development and is associated with learning and memory, but a causal connection has not been established. Here, it is reported that neurons and astrocytes expressing IGFBP2 are distributed throughout the hippocampus. IGFBP2 enhances excitatory inputs onto CA1 pyramidal neurons, facilitating intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 39 publications
(122 reference statements)
1
21
0
Order By: Relevance
“…In another study, prolonged hypoxia led to enhanced expression of IGFBP-2 with extensive neuronal loss in the ligated hemisphere as compared to the control hemisphere. Therefore, hypoxia leads to alterations in IGFBP-2 expression (41, 64). Different patterns of IGFBP-2 expression associated with different degrees of injury suggest that IGFBP-2 may contribute to neuronal rescue and/or brain repair processes [Figure 3; (65)].…”
Section: Neurotropic and Regenerative Functions Of Igfbp-2 In Cnsmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study, prolonged hypoxia led to enhanced expression of IGFBP-2 with extensive neuronal loss in the ligated hemisphere as compared to the control hemisphere. Therefore, hypoxia leads to alterations in IGFBP-2 expression (41, 64). Different patterns of IGFBP-2 expression associated with different degrees of injury suggest that IGFBP-2 may contribute to neuronal rescue and/or brain repair processes [Figure 3; (65)].…”
Section: Neurotropic and Regenerative Functions Of Igfbp-2 In Cnsmentioning
confidence: 99%
“…For IGFBPs binding to IGF-IR, a single detergent molecule contacts residues known to be critical (111). Proteolytic degradation of IGFBP-2 near cell surface receptors has lower affinity for IGFs and thus by competing with IGFs, HBD of IGFBP-2 may bind with that detergent molecule in IGF-IR to initiate downstream signaling via autophosphorylation of the receptor (41). Moreover, the presence or absence of sialic acid residue in the IGF-IR may be another factor for interaction with IGFBP-2.…”
Section: Possible Functions Of Igfbp-2 In the Hippocampusmentioning
confidence: 99%
See 2 more Smart Citations
“…For example : colorectal cancer(14), hepatocellular carcinoma(15), bladder cancer (16), breast cancer (17), etc. In addition,a study suggests that increased expression of IGFBP2 in the hippocampus during neonatal development is associated with learning and memory, which provides insights into the cognitive needs of IGFBP2 in early life (18). In the eld of cardiovascular disease, Han et al found that microRNA-873 alleviated myocardial damage in gestational diabetic rats by upregulated IGFBP2 (19).However, there are limited studies on the relationship between IGFBP2 and atrial brillation.…”
Section: Discussionmentioning
confidence: 99%